Influência de diferentes aparelhos fotoativadores LED sem fio e o nível de bateria nas propriedades da resina composta - Cardoso, Igor Oliveiros (2018)
Light cure unit (LCU) may exhibit different and varying irradiance values as it is discharged. The aim of this study was to evaluate the influence of different light emitting diodes (LEDs) and battery level on the properties of composite resins. First, the irradiance and the number of cycles of each device were checked, until the battery was completely discharged. After evaluating the 5 LEDs, being Optlight Color (Gnatus), Bluephase (Ivoclair), Valo (Ultadent), Radii Plus (SDI) and Radii Expert (SDI), resin disks (Aura, DC1, SDI) were prepared by varying the battery level of the devices: high level (100%), medium level (50%) and low level (10%). The degree of conversion, diametral tensile strength, sorption and solubility were tested. Data were checked for homoscedasticity and submitted to two-way ANOVA and three-way ANOVA depending on the test performed, followed by the Tukey test with significance level of 95% (α <0.05). Correlations between the irradiance and number of cycles were checked by Pearson correlation test. There was a positive correlation between irradiance and cycles of light curing. Valo and Radii Expert was the only unit that was not influenced by the battery level in any test. Optlight Color presented better results than other LEDs, or even equal, in almost all categories tested. Thus, different LED units at different battery levels can influence the degree of conversion, diametral tensile strength, sorption and solubility of the composite resin.